HYPNO-BREASTFEEDING REDUCES ANXIETY OF BREASTFEEDING MOTHERS DURING THE COVID-19 PANDEMIC - Witari, Ni Nyoman Deni; Arini, Ketut Novia; Widiastuti, Ni Made (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: COVID-19 pandemic is a time when a lot of people are vulnerable for virus transmission which can cause anxiety and psychological disorders, including for postpartum and breastfeeding mothers. The harmful effects of postpartum anxiety, if not managed properly, can affect the physical and psychological health of both mother and baby. The purpose of this study was to determine the effect of hypno-breastfeeding on reducing postnatal maternal anxiety.Methods: The design of this study was quasi-experimental design with one pretest-posttest group, without control group. This study was conducted at the South Denpasar Health Center III with samples of 32 respondents who met the inclusion criteria. The sampling technique used in this research was purposive sampling. The independent variable in this study was hypno-breastfeeding and the dependent variable was decreased anxiety. Data were collected using the Zung Self-rating Anxiety Scale (ZSAS) questionnaire and data analysis was carried out using univariate and bivariate test (t test).Result: The results showed that most of the breastfeeding mother before being given hypno-breastfeeding (65%) experienced moderate anxiety and after being given hypno-breastfeeding, most mother (47%) experienced mild anxiety. The bivariate results show the t-count value of 6.851 with p-value (0.000) which showed that there is a significant effect of hypno-breastfeeding on reducing anxiety of breastfeeding mothers.Conclusion: Hypno-breastfeeding can be applied to breastfeeding mothers to reduce anxiety and make exclusive breastfeeding successful.